Large copy number variants are an important cause of congenital hyperinsulinism that should be screened for during routine testing - Flanagan, Sarah E.; Lazaridi, Isabella-Anna; Männistö, Jonna M. E.; Bennett, Jasmin J.; Kalyon, Oguzhan; Johnson, Matthew B.; Wakeling, Matthew N.; Houghton, Jayne A. L.; Laver, Thomas W. (Frontiers in Endocrinology, 2025)
IntroductionCongenital hyperinsulinism (HI) is characterized by inappropriate insulin secretion from the pancreatic beta-cells which causes severe hypoglycemia. Copy number variants (CNVs) encompassing multiple genes (contiguous gene CNVs) can cause syndromic forms of HI although they are not typically screened for during routine genetic testing for this condition. We aimed to assess the prevalence of disease-causing contiguous gene CNVs in a cohort of individuals referred for HI genetic testing.MethodsOur cohort consisted of 3,763 individuals, of which 1,916 had received a genetic diagnosis for their HI and 1,847 were genetically unsolved following routine testing. We screened for 6 different contiguous gene CNVs using next-generation sequencing data from all individuals in the genetically unsolved cohort and searched for patients in our solved cohort who had already been found to have one of these CNVs.ResultsWe identified a contiguous gene CNV affecting 5 of the 6 genomic loci in 53 probands; 28 from the solved cohort and 25 from the genetically unsolved cohort. Variants on the X chromosome were most common, being detected in 24/53 children. Overall, these variants represented 2.7% (53/1,941) of genetic diagnoses, which is similar to the prevalence of variants in other commonly screened HI genes.DiscussionThese results confirm that contiguous gene CNVs are an important cause of HI which should be included in standard gene panel testing processes as this will improve pick-up rates for genetic diagnoses in HI.